Mainstreaming One-Health Concept & Approach into postgradute research - Damba, Osman Tahidu (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Mainstreaming One Health into general agricultural and food security intervisions seeks to provide a onestop solution to addressing the current effects of climate change. While focus is farmers and other users, the needs to identify and capacitate future researchers and practionners with adequate knowledge will augment the already exiting approaches. One health ontroduction into research, teaching and community services has redefined research in the agriculture and climate change space. This has created a nexus which AICCRA sponsored students unpacking through research. Capacity trainings and seminar presentations has provided feedback on how One health is required for research output.